Tuning of Velocity PID-Fuzzy Power System Stabilizer by Particle Swarm Optimization - Elmenfy, Tawfiq; Abdelsalam, Samah (Libyan Journal for Engineering Research, 2017)
Power system stabilizer (PSS) is used to damping power system oscillation. It will act as supplementary feedback through the generator excitation system, which produce a component of electrical torque in phase with speed variation. Fuzzy controllers are nonlinear. It is more difficult to set the fuzzy controller gains compared to conventional PID controller. This research proposed velocity (PID-FPSS) its gains are tuned by particle swarm optimization technique (PSO). The objective is to damp local-area oscillation that occur following power system small or large disturbances. The effectiveness of the proposed technique is illustrated by applying the velocity PID-FPSS to a single-machine infinite bus power system that is typically used in the literature to test the performance of power system stabilizers. The simulation has been conducted in MATLAB, SIMULINK (R2013a) package. A comparison between the proposed PID-FPSS and a well-designed robust power system stabilizer (RPSS) confirms the superiority of the proposed technique.